Knowledge and Attitude on Pubertal Changes among Adolescents in a Government School of Biratnagar - Karki, Pooja; Dahal, Tulasha (Medha: A Multidisciplinary Journal, 2023)
Adolescence typically describes the years between ages 10 to 19 and is considered to be critical transitional stage from childhood to adulthood characterized by onset of puberty. Adolescence can be a time of both disorientation and discovery which contributes adolescents to unfavorable attitude and suffer from anxiety, depression, substance use disorder, etc. The main objective of the study is to assess knowledge and attitude on pubertal changes among adolescents. A descriptive cross sectional study design was used. Non-probability purposive sampling method was used to select setting whereas simple random lottery method was adopted to select 1 section from each grade and total enumeration method was used to select the sample where 139 adolescents studying grade 8,9 and 10. Data was collected by self-administer semi-structure questionnaire method. Analysis of data was done using SPSS16 version and descriptive statistics mean, median, standard deviation, frequency, percentage and chi-square test was used to find the association between dependent and independent variables The findings of the study revealed that (64.7%) adolescents give correct meaning about puberty, 28.8 % adolescents had knowledge about reason of pubertal change is due to sex hormones and 78.45% of adolescents had knowledge that menstruation is regular monthly bleeding from vagina. Regarding level of knowledge42.4% of the respondents had below average level of knowledge whereas only (7.2%) had very good knowledge regarding pubertal changes. Similarly, majority of the respondents (96.4%) moderately favorable attitude and only (2.9%) had unfavorable attitude towards pubertal changes.